Fenomena Pendidikan Elitis dalam Sekolah/Madrasah Unggulan Berstandar Internasional - Prastowo, Andi (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
This article aims to review and discuss the phenomenon of eminent school/ madrasah in international standards in Indonesia that has a tendency to be elitist and the reproductive force is not productive force. There are two formulations of the problem studied in this article, namely how elitism emerges in the eminent school/madrasah in international standards? Then, how to recommend the eminent school/madrasah in order to ensure equitable access to education for all children throughout the community of nations, especially among the poor?